Spatial behavior of corn leaf aphid and syrphid flies in corn crop in the northeast of Pará - Nascimento, José Marlon dos Santos; Martins, Ivan Carlos Fernandes; de Mello, Marcello Neiva; da Silva, Jhonatan Rocha; Lima, Maria Milena Oliveira; Oliveira, Fábio Júnior de; Campos, Lourival Dias (EntomoBrasilis, 2020)
The aim of this study was to verify the spatial and temporal behavior of corn leaf aphid (Rhopalosiphum maidis Fitch.) and hoverflies in corn crop in the municipality of Igarapé-Açu, northeast of Pará, Brazil, as well as the influence of adjacent areas on the occurrence of these insects. An experimental area of 1.0 ha (100 x 100 m) was used in the years 2015 and 2016, adjacent areas consisted of mango agroecosystem, pasture and secondary forest. The area was divided into grid with 100 plots of 100 m² (10 x 10 m). Ten plants were randomly selected, totaling 1,000 plants per sampling date. Corn leaf aphid colonies (= or> 15 aphid) and syrphid flies adult was visually analyzed throughout the aerial parts of the plants. The spatial behavior was analyzed by semivariogram modeling and kriging interpolation maps. The semivariograms and kriging maps were made by the R software for Windows. Gaussian, spherical and exponential models were the best fit for corn leaf aphid in both harvests, showing aggregate behavior. The strong and moderate spatial dependence index prevailed, with range ranging from 12.46 to 93.04 m for R. maidis. The syrphids flies showed spatial interaction with the corn leaf aphid and they also show aggregate behavior, confirmed by most adjustments in the spherical and exponential models. The spatial dependence index of the prevailing syrphids flies were moderate and weak, ranging from 14.00 to 101.33 m. Adjacent areas showed influence on occurrence and dispersal of both corn leaf aphid and syrphids flies.